2020
DOI: 10.1002/nml.21417
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit governance and outside corruption: The role of accountability, stakeholder participation, and management systems

Abstract: Outside corruption implies that a nonprofit organization is used to commit an infraction or crime. In Spain, this type of corruption has been detected in the context of public nonprofits as a result of the legal reform that enabled the judgment of the criminal responsibility of legal entities. A large percentage of these entities were affected by the reform, but little is known about the possible practices that can altogether prevent this behavior. In particular, there are few studies that consider nonprofit g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Finally, broadening the scope of our research, peer regulation may be an effective means to strengthen INGOs' mission orientation not only in the context of economic and political pressures. For instance, López‐Arceiz and Bellostas (2020) find that nonprofits employ different governance mechanism to withstand external pressures to engage in corrupt behavior. The study shows that internal mechanisms such as stakeholder participation and sound management systems can reduce corrupt behavior of nonprofits.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, broadening the scope of our research, peer regulation may be an effective means to strengthen INGOs' mission orientation not only in the context of economic and political pressures. For instance, López‐Arceiz and Bellostas (2020) find that nonprofits employ different governance mechanism to withstand external pressures to engage in corrupt behavior. The study shows that internal mechanisms such as stakeholder participation and sound management systems can reduce corrupt behavior of nonprofits.…”
Section: Discussionmentioning
confidence: 99%
“…Our review captured a range of articles examining transparency (Nezhina & Brudney, 2012;Phillips, 2019), governance (Abu Khadra & Delen, 2020;Gibelman et al, 1997;Gibelman & Gelman, 2001, 2002a, 2002bHarris et al, 2017), and accountability practices (Andreoli & Lefkowitz, 2009;Gibelman & Gelman, 2004;Greenlee et al, 2007;Holtfreter, 2004Holtfreter, , 2008Kummer et al, 2015;LeClair, 2019a;López-Arceiz & Bellostas, 2020;Ohalehi, 2019;Zuber & Andersen, 2020). Nevertheless, the empirical focus of our review, tight definition of nonprofit scandal, and selection of search terms may all have contributed to an underemphasis of important allied work in these areas (readers interested in learning more about this allied work should see, for example, Ben-Ner & Van Hoomissen, 1994;Bies, 2010;Farwell et al, 2019;Harris & Neely, 2018;Leardini et al, 2016;Saxton & Guo, 2009;Van Puyvelde, 2016;Van Puyvelde et al, 2011).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As stated by López-Arceiz and Bellostas [33], nonprofit organization leaders should promote good governance to increase trust among stakeholders and mitigate fraud. Nonprofit leaders or managers have the mission to assess employees, donors, and government officials' attitudes and behaviors toward their organizations to ensure the credibility of the organization when collecting and managing the funds received from donors [33]. The findings from the interviews indicated that participants wanted to understand employees, donors, and government officials' attitudes about fraud in their organizations (Table 1).…”
Section: Stakeholders' Attitudes and Behaviorsmentioning
confidence: 99%